PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN PRESTASI BELAJAR KIMIA SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) KELAS XI SMAN 14 PEKANBARU - Titis Sarisna Wahid; Rini '; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research has been done by applying cooperative learning model Team Games Tournament (TGT) to improve student achievement on the subject of solubility and solubility product concept (Ksp) at 11th of SMA Negeri 14 Pekanbaru. This type of research is an experimental research conducted in the second semester of the academic year 2014/2015. The sample consisted of two classes, XI IPA3 as an experiment class and XI IPA2 as a control class. The data collection technique is a technique tests. The data collected was obtained from tests homogeneity and difference between the value pretest posttest with a hypothesis test data. Data were analyzed by t-test were used to determine the increase learning achievement between the experimental and control classes. From the research results can be concluded that the application of cooperative learning model Team Games Tournament (TGT) can improve student achievement on the subject of solubility and solubility product concept (Ksp).Keyword : Cooperative Learning Model, Cooperative Learning Model TGT, Student’s Achievements